Intramammary Infections in Heifers—Time of Onset and Associated Risk Factors - Julia Nitz; Volker Krömker; Doris Klocke; Nicole Wente; Yanchao Zhang; Martin tho Seeth (Animals, 2020)
To reduce the negative effects of mastitis in dairy heifers in early lactation on the future milking performance, the aim of this study was to define the time-related period of intramammary infections and to relate this to risk factors at heifer and quarter level for intramammary infections and subclinical mastitis. In total, 279 German Holstein Frisian heifers in three farms in Northern and Eastern Germany were included in this study. Quarter milk samples for cytomicrobiological examination were collected 3 ± 1 days after calving and 17 ± 3 days after calving, and risk factors at heifer and quarter level associated with intramammary infections and clinical mastitis were recorded during the trial period. Data were analyzed using logistic regression procedures and odds ratios were calculated. Calving at older ages increased the odds of intramammary infections with non-aureus staphylococci (NAS) and coryneforms 17 ± 3 days after calving compared to heifers calving at a younger age. Detaching of milking cups during milking is a risk factor for new infections between day 3 ± 1 and 17 ± 3 postpartum. The milk yield after calving is associated with a decrease in intramammary infections with environmental pathogens and clinical mastitis. A high milk yield assists the development of udder edema with an increased risk of intramammary infections with NAS and coryneforms. An increased somatic cell count (SCC) after calving increased the odds of intramammary infections with contagious pathogens 17 ± 3 days postpartum. The early lactation has an important influence on udder health and intramammary infections postpartum in dairy heifers. Udder quarters eliminated pathogens during early lactation by 6.9% for cases in this study. New infections manifest themselves up until 17 ± 3 days postpartum, especially with Corynebacterium spp. and NAS. In total, 82.9% of the infected quarters showed new infections with another pathogen species 17 ± 3 days postpartum than 3 ± 1 days postpartum. In conclusion, the early lactation has an important influence on udder health and intramammary infections postpartum in heifers with the possibility that udder quarters eliminate pathogens, but also the danger that new infections manifest themselves. Thus, the prevention of new infections by minimizing the associated risk factors is of great importance.